TINJAUAN LITERATUR UNTUK DESAIN ULANG JABATAN DI ERA DIGITAL - Fajar Saputra; Febrina Pinkan, Netty Merdiaty (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
In the era of industrial revolution 4.0, technological advances have changed the way organizations work. Job redesign to improve efficiency and adaptation to technology is influenced by transformations such as innovation and automation. By analyzing ten relevant journals, this study examines the importance of job redesign in the digital age. Results show that job redesign improves performance, job satisfaction and employee motivation. Continuous training also helps employees adjust to technological advancements. In today's technological era, job redesign is an important strategy to keep companies operating